Challenges of Upgrading Local Cattle with Exotic Breeds: Genetic, Environmental, Economic, and Sustainability Trade-offs - Md. Emran Hossain (International Journal of Molecular Biotechnological Research, 2025)
The practice of upgrading local cattle with exotic breeds has gained popularity as a strategy to enhance milk and meat production. While this approach holds potential for improving productivity, it also presents a range of challenges that need careful consideration. This study examines the genetic, environmental, economic, and sustainability trade-offs associated with upgrading local cattle with exotic breeds. From a genetic perspective, upgrading can result in the dilution of traits specific to indigenous breeds, such as disease resistance and adaptability to local conditions. Environmental challenges arise from the reduced resilience of crossbred animals to harsh climates and resource-limited environments, necessitating more intensive management practices. Economically, upgrading often leads to increased input costs, including feed, healthcare, and specialized breeding programs, which may not be sustainable in low-resource farming systems. Furthermore, the long-term sustainability of upgrading efforts is questioned due to the risk of genetic erosion and the dependence on external resources. This study highlights the complexities of upgrading and emphasizes the need for balanced approaches that consider both the potential benefits and the inherent limitations of such practices. Recommendations for policy and management strategies are provided to mitigate the adverse effects and ensure that upgrading initiatives align with sustainable livestock development goals.
Keywords: Environmental impact; Milk Production; Sustainability; disease resistance; genetic erosion; local breeds; reproductive health; upgrading